Virtual Reality Exposure Therapy to Overcome Fear of Covid-19: A Systematic Literature Review - Annastasia Ediati; Norhendra Ardhanaputra; Putri Kurnia Intansari; Dian Veronika Sakti Kaloeti; Kurniawan Teguh Martono (Proceedings of International Conference on Psychological Studies (ICPSYCHE), 2022)
Virtual Reality Exposure Therapy (VRET) is a psychological approach that may provide users with therapeutic immersed experience to interact with feared stimuli and situations with technological support. Covid-19 pandemic had given rise to extraordinary fears and many serious psychological impact for people around the world that need to be overcome. This study aims to find out the effectiveness of Virtual Reality Exposure Therapy (VRET) in helping to overcome Fear of Covid-19 and to explore relevant situation for treatment procedure. Systematic literature review used with PRISMA guidelines to conduct journal searches through some online database portals. Obtained journals will be selected based on inclusion and exclusion criteria with four selection stages, namely identification, screening, eligibility and included. The results showed the potential of VRET had a significant effect in helping to overcome the fear of Covid-19. However, this spesific topic is still rarely studied and further study need to be done to develop more reliable VRET treatment.